Couple relationship problems—a task for the general practitioner? A cross-sectional survey from Norway - Berge, Siri Dalsmo (Fam Pract, 2020)
BACKGROUND: A healthy couple relationship is a predictor of good health. There is a lack of knowledge about what role family and couples counselling should have in general practice. OBJECTIVES: To identify the prevalence of patients who have talked, or want to talk, with their general practitioner (GP) about their couple relationship, to investigate what characterizes these patients and to explore whether they believe that couple relationship problems should be dealt with in general practice. METHODS: We conducted a cross-sectional survey in 70 general practices in Norway during spring 2019. A questionnaire was answered by 2178 consecutive patients (response rate 75%) in GP waiting rooms. Data were examined using frequencies and linear and logistic regression models. RESULTS: We included 2097 responses. Mean age was 49.0 years and 61.3% were women. One in four (25.0%) had already talked with their GP about couple relationship problems, while one in three (33.5%) wanted to talk with their GP about their couple relationship problems. These patients more frequently had experience of divorce, poor self-rated health, an opinion that their couple relationship had a significant impact on their health and lower couple relationship quality when adjusted for age, sex, present marital status and children living at home. We found that 46.4% of patients believed that GPs should be interested in their couple relationship problems. CONCLUSION: Relationship problems are frequently addressed in general practice. GPs should be prepared to discuss this issue to facilitate help for couples earlier than they might otherwise expect.